Treadmill running on neuropathic pain: via modulation of neuroinflammation - He, Wei-Chun; Hou, Shuang-Long; Wang, Kai-Bin; Xu, Ning; Li, Ke; Xiong, Ting; Luo, Jing (Frontiers in Molecular Neuroscience, 2024)
Neuropathic pain is a type of chronic pain caused by an injury or somatosensory nervous system disease. Drugs and exercise could effectively relieve neuropathic pain, but no treatment can completely stop neuropathic pain. The integration of exercise into neuropathic pain management has attracted considerable interest in recent years, and treadmill training is the most used among exercise therapies. Neuropathic pain can be effectively treated if its mechanism is clarified. In recent years, the association between neuroinflammation and neuropathic pain has been explored. Neuroinflammation can trigger proinflammatory cytokines, activate microglia, inhibit descending pain modulatory systems, and promote the overexpression of brain-derived neurotrophic factor, which lead to the generation of neuropathic pain and hypersensitivity. Treadmill exercise can alleviate neuropathic pain mainly by regulating neuroinflammation, including inhibiting the activity of pro-inflammatory factors and over activation of microglia in the dorsal horn, regulating the expression of mu opioid receptor expression in the rostral ventromedial medulla and levels of γ-aminobutyric acid to activate the descending pain modulatory system and the overexpression of brain-derived neurotrophic factor. This article reviews and summarizes research on the effect of treadmill exercise on neuropathic pain and its role in the regulation of neuroinflammation to explore its benefits for neuropathic pain treatment.